Street Vendors Hypergrowth: Consequence of Uncontrolled Urbanization In Semarang City - Sariffuddin, Sariffuddin; Wahyono, Hadi; Brotosunaryo, Brotosunaryo (Komunitas, 2017)
This paper aims to understand the role of urbanization in the emergence of in urban area street vendors. In the case of Semarang, more than 54% of its street vendors come from its hinterlands. These sectors turn to development dichotomy that have a positive and negative impact. Positively, this area becomes people’s economic resilience. In the negative side, more than 60% of vendors make their stall in the public space. This research uses a mix-method approach taking 271 samples, Focus Group Discussion (FGD) and in-depth interview. From this study, it can be concluded that urbanization has led to the outbreak of street vendors through (1) rural-urban migration, and (2) social change as a result of gentrification. Working as street vendors turned out to be an alternative way of life to adapt to global economic uncertainty. Also, there are 71.6% of street vendors open their stalls in 2003-2009, or about 6-7 years after the monetary crisis (1997). It shows that the financial crisis is not the primary trigger for the outbreak of street vendors. Another interesting finding is that there is a new phenomenon in the form of the intervention of the middle class who took part in this business.